Analyzing scenarios and designing initiatives toward just transitions: coproducing knowledge with(in) the dried fish sector in the Indian Sundarbans - Ghosh, Raktima; Mukherjee, Jenia; Bandyopadhyay, Aishik; Chatterjee, Subhradeep; Choudry, Anuradha; Ghosh, Poulami; Pathak, Souradip; Sen, Amrita; Sinha, Priyadarsini (Frontiers in Water, 2023)
The south-western frontier of the Indian Sundarbans accommodates an array of fish drying collectives which are now exposed to a bundle of mutually reinforcing social-ecological-institutional challenges. Despite its widening contribution to regional-global food demand and livelihoods, the significance and labour arrangements within the dried fish value chain have received rare attention in research and lack recognition in policy circles. As part of the Social Sciences and Humanities Research Council (SSHRC) sponsored Dried Fish Matters global partnership project, our research team addresses this gap in two ways: i) delineating knowledge base through a systematic literature review on interfacing social-ecological and sociohydrological dimensions in fisheries and dried fish, and ii) deploying a knowledge co-production approach involving the participation of multiple stakeholders, researchers, partner NGO, and scientists for meaningful understandings about the constraints and potentials in the sector. With detailed lessons from the field, our interdisciplinary research team acts as a liaison among actors to build a collaborative platform, identify prevalent adaptive practices and co-design pathways for short-, intermediate- and long-term interventions through which the fish drying practices can be more effectively improvised upon and up-scaled. This essay lays out detailed insights and sensible recommendations from the knowledge co-production workshop on climate-resilient dried fish practices in the Indian Sundarbans, which was co-organized as a part of action-oriented participatory research that stands out to be relevant and timely within the global scenario of Blue Justice. Grounded on the crisscrossing conceptual, empirical, and collective observations on dried fish resource system, the authors advocate for (col)laboratory research rationale and praxes in forging just transitions for the less explored dried fish sector.